Risk Factors for Syphilis at a Large Urban Emergency Department. Issue 2 (1st September 2021) - Ford, James S.; Shevchyk, Ivan; Yoon, Joseph; Chechi, Tasleem; Voong, Stephanie; Tran, Nam; May, Larissa
Abstract : Undomiciled housing status, history of HIV, history of tobacco use, and history of illicit drug use were independently associated with a new diagnosis of syphilis in the emergency department. Supplemental digital content is available in the text. Abstract : Background: The prevalence of syphilis is increasing in the United States. The emergency department (ED) is an important setting to screen and treat underserved populations. To tailor testing protocols to the local population, we aimed to identify risk factors for syphilis positivity in ED patients. Methods: We performed a retrospective analysis of ED patients who were screened for syphilis between November 2018 and August 2020. Patients were screened for Treponema pallidum antibody using a multiplex flow immunoassay, and positive results were confirmed by rapid plasma reagin or T. pallidum particle agglutination. Risk factors for new syphilis diagnoses were identified using multiple logistic regression. Results: We screened 1974 patients for syphilis (mean age, 37 ± 16 years; 56% female). We identified 201 patients with new infections without previous treatment. Independent risk factors for a new diagnosis of syphilis included housing status (undomiciled, 23% [60 of 256]; domiciled, 9% [133 of 1559]; adjusted odds ratio [aOR], 1.9 [95% confidence interval CI, 1.2–3.0]), history of HIV (positive, 44% [28 of 63]; negative, 9% [173 of 1893]; aOR, 5.8 [95% CI, 3.0–11.2]), tobacco use (positive, 15% [117 of 797]; negative, 4% [29 of 665]; aOR, 2.4 [95% CI, 1.5–3.9]), and illicit drug use (positive, 14% [112 of 812]; negative, 8% [52 of 678]; aOR, 2.2 [95% CI, 1.0–2.5]). Conclusions: Undomiciled housing status, history of HIV, history of tobacco use, and history of illicit drug use were independently associated with a new diagnosis of syphilis in the ED. Broadening targeted syphilis screening algorithms beyond sexually transmitted disease–related complaints could help identify new syphilis cases for treatment.